Assessing the potential of mangrove educotourism to marine protected area: a case of Tioman and Tulai Islands, Pahang, Malaysia - Saad, Shahbudin; Ahmad, Zuhairi; Mohammad Noor, Normawaty; Mukai, Yukinori (Scientific Research Publishing, 2015)
Mangroves composition and species are richly diverse in Tioman and Tulai Island. A total of 23 mangrove species have been found consisting of exclusive and non-exclusive species in Kg. Juara, Kg. Nipah, Kg. Paya, Kg. Genting and Tulai Island. The abundance mangrove species are Rhizophora X lamarckii, Rhizophora apiculata, Rhizophora mucronata and Brugueira gymnorrhiza. From supervised classification, total of 59.90 hectares mangrove covers have been identified in both islands, with 86.49% in Tioman Island (52.76 hectares) and 13.51% in Tulai Island (7.14 hectares). A new hybrid species has been found (Rhizophora Xlamarckii) dominated in Tulai Island, combination between Rhizophora stylosa and Rhizophora apiculata. At the mean time only mangrove area in Teluk Bakau, Tulai Island is considered as the focal destination of tourists to the area. However, other mangrove areas in Tioman Island are also potential to be promoted as tourist destination areas. Although the mangrove area is only a part of the scenery, its presence obviously enhances tourist attraction. The basic facilities such as information counter, walking trails, garbage boxes and toilets are considered necessary. The main information panel and site map should be provided on the mangrove sites. Boardwalks may be constructed for visitor to access the mangrove area without destroying the root system and stand. The actual site of these facilities and on-site information guides should be strategically placed in order to provide beneficial information and as well as to sustain the biophysical stability of the sites. Since mangroves provide various important functions in nature, it hopes that the mangrove educotourism activity will influence the people and community’s attitudes to the environment, conservation and sustainable development in a very positive way.